Aktualisasi Akad dalam Fikih Muamalah bagi Lembaga Keuangan Syariah - Prawiro, Atmo (Tasyri' : Journal of Islamic Law, 2022)
This study aims to explore the principles of contract in Fiqh Muamalah which are practiced in sharia business. The contract is binding between two or more parties who make a binding agreement. Whereas the principles of agreement (akad) in sharia business are basically taken from the sources of fiqh muamalah itself, then applied in the field of modern sharia business, giving rise to various perceptions about the distribution of agreements (akad) based on the object of the agreement (akad). The research method used in this study is descriptive qualitative critical analytic, intended to provide an analytical description of the form of application of contract theories in muamalah fiqh for Islamic financial institutions. Through an analytical approach, methodologically it can be seen the application of contract theory with the support of studies on Islamic financial institutions. The approach used in this study, namely the philosophical and juridical approach of Islamic law. This study found that the more honest the sharia business parties in the contract will affect the religious behavior of the parties. This study also explains that the entrance to sharia or not sharia business starts from a strong intention of making an act, and this is in accordance with the rules of Innama al-'a'malu bi al-niyyat.